If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) + 2x = 6(x + 1) + -10 Reorder the terms: 3(-3 + x) + 2x = 6(x + 1) + -10 (-3 * 3 + x * 3) + 2x = 6(x + 1) + -10 (-9 + 3x) + 2x = 6(x + 1) + -10 Combine like terms: 3x + 2x = 5x -9 + 5x = 6(x + 1) + -10 Reorder the terms: -9 + 5x = 6(1 + x) + -10 -9 + 5x = (1 * 6 + x * 6) + -10 -9 + 5x = (6 + 6x) + -10 Reorder the terms: -9 + 5x = 6 + -10 + 6x Combine like terms: 6 + -10 = -4 -9 + 5x = -4 + 6x Solving -9 + 5x = -4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -9 + 5x + -6x = -4 + 6x + -6x Combine like terms: 5x + -6x = -1x -9 + -1x = -4 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 + -1x = -4 + 0 -9 + -1x = -4 Add '9' to each side of the equation. -9 + 9 + -1x = -4 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = -4 + 9 -1x = -4 + 9 Combine like terms: -4 + 9 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| 87-2x=25x+15 | | -10-10x=200-45x | | 4x+12=-47-7x | | (576/625)((1/12)-(49/6912)) | | 6-7x=114-28x | | -169=9x+10x+21 | | 9c+4=5c+3a | | 4x+9=-47-7x | | x-4y+14=0 | | 7+8x=91 | | x+.06x=8098 | | 9(x+3)+3(2x+1)= | | (1/12)+(1/x)=(1/14)+(1/(x-4)) | | 14-3(3-2x)=23 | | 9/10a+7=4/5a | | x^2-3x=104 | | 576/625(12-(-49/6912)) | | 3n-8=-19 | | 25+0.15m=71.8 | | 71.8m+25=0.15 | | 7x-10y=20 | | (12+x)/2=15 | | 3(2x-4)-4=3(x-2)+11 | | 4x+8=10(x-1) | | 25m+0.15=71.8 | | (4g+7)(4g-7)= | | 8x-(4x+2)=6x-36 | | 30=w/6 | | z+9c=27 | | 24=m(4)+20 | | 1/2(7(-7/12)+48) | | 24=m(4)-20 |